Ludwig Senfl (c.1490–1543). A Catalogue Raisonné of the Works and Sources - Gasch, Stefan; Tröster, Sonja; Lodes, Birgit (Brepols, 2020)
Until now, scholars have had an inadequate picture of the scope and transmission of the œuvre of Ludwig Senfl (<span class=